Laporan Kasus Berbasis Bukti: Akurasi Diagnostik RT-PCR Spesimen Saliva terhadap Spesimen Swab Nasofaring pada Suspek COVID-19 - Jason Theola; Ananda Maulana Fanshur; Muhammad Rayyan Faher Shahab; Nico Gamalliel (Majalah Kedokteran Indonesia, 2021)
Introduction: Nasopharyngeal swab followed by RT-PCR has become the gold standard in diagnosing COVID-19. This method is difficult to perform because the procedure is inconvenient for the patient. There is another diagnostic method using saliva as an RT-PCR specimen.Objective: To determine the diagnostic accuracy of saliva specimen RT-PCR in diagnosing COVID-19 compared to nasopharyngeal swab specimens as the gold standard.Methods: Literature searching was performed by searching literature through MEDLINE, EBSCO, and Scopus. The articles selected were diagnostic or cross-sectional studies containing sensitivity, specificity, prevalence data, and appropriate to our PICO and eligibility criteria. A critical appraisal was performed after obtaining the selected articles.Results: Six articles were critically appraised. All articles showed that the saliva sample used for RT-PCR in diagnosing COVID-19 had good diagnostic accuracy.Conclusion: Saliva specimen to diagnose COVID-19 can replace nasopharyngeal swab specimen because it has comparable diagnostic accuracy with the gold standard. It is also a non invasive method which is more convenient for patients.